A hybrid approach for an oil and gas company as a representative of a high reliability organization. Issue 3 (3rd July 2021) - Rivera, Gustavo; Yunusa-Kaltungo, Akilu; Labib, Ashraf
Abstract: A hybrid method combining various Reliability (Fault Tree Analysis -FTA-, Reliability Block Diagrams -RBD), Multi Criteria Decision Making (Analytic Hierarchy Process -AHP), High Reliability Organisations (HROs) and Learning from Failures (LFF) framework tools, has been applied to a long-established pattern of small to medium chronic failures in a large Oil & Gas organisation. Through the Reliability techniques FTA/RBD, the root causes of the chronic failure pattern were identified, categorised and their interconnections established. The obtained root causes were then used as criteria and with the five principles of mindful organising as alternatives in constructing the AHP model. Finally, an attempt to extract useful generic lessons from the failure causes identified by applying the learning from failure (LFF) principles was made, in order to obtain guidelines for updating existent company routines. Despite a few shortcomings, some inherent to the tools themselves and some related to the method intent, reasonable results were obtained which appear to demonstrate the applicability of the approach. Abbreviations: AHP: analytical hierarchy process; CAPEX: capital expenditure; CBM: condition based maintenance; CTA: crisis tree analysis; CMMS: computerised maintenance management system; DMG: decision making grid; E&P: exploration and production; FTA: fault tree analysis; HRO: high reliability organisation; LFF: learning from failure; MCDM: multi criteria decision making; OPEX: operational expenditure; PSF: performance shaping factors; RACI: responsible accountable consulted informed; RBD: reliability block diagram; RBM: risk based maintenance.